Safety, Health, and Nutrition in Early Childhood Education - Paris, Jennifer (Open textbook library., 2018)
Early childhood is a critical time in development. Many outcomes, both positive and negative, have their beginnings in these years. It is vital that children’s health and safety be protected. High-quality early care and education programs can play a valuable role in improving outcomesfor children.